The Effect of Financial Literacy and Online Shopping on Student Consumptive Behavior - Siti Azsahrah; Jumawan Jasman; Asriany; Muhammad Anugrah Ardhana (Jurnal Economic Resource, 2023)
This study aims to determine the effect of financial literacy and online shopping on student consumptive behavior. This research method is quantitative using primary data with survey techniques using an online questionnaire tool on Google form with measurements using a Likert scale with a population of respondents in this study of 85 students of Muhammadiyah University of Palopo. The sample collection technique was carried out using the Slovin Method. The data analysis used was descriptive analysis, multiple linear regression analysis, Validity test, Reliability test, coefficient of determination, hypothesis test and F statistic test. The data analysis technique used was multiple linear regression analysis using the SPSS 25 application. The results showed that the independent variable Financial Literacy had a positive effect on Student Consumptive Behavior. This could be seen at a significant 0.002 <0.05, meaning that there was a positive and significant influence on Student Consumptive Behavior. And the Independent Online Shopping Variable has a positive and significant effect on Student Consumptive Behavior. This can be seen at a significant 0.000 <0.05 meaning that there is a positive and significant influence on student consumptive behavior.